Soil and land use research in Europe: lessons learned from INSPIRATION bottom-up strategic research agenda setting - Bartke, Stephan; Boekhold, Alexandra E.; Brils, Jos; Grimski, Detlef; Ferber, Uwe; Gorgon, Justyna; Guérin, Valérie; Makeschin, Franz; Maring, Linda; Nathanail, C. Paul; Villeneuve, Jacques; Zeyer, Josef; et al. (Elsevier, 2018)
We introduce the INSPIRATION bottom-up approach for the development of a strategic research agenda for spatial planning, land use and soil-sediment-water-system management in Europe. Research and innovation needs were identified by more than 500 European funders, endusers, scientists, policy makers, public administrators and consultants. We report both on the concept and on the implementation of the bottom-up approach, provide a critique of the process and draw key lessons for the development of research agendas in the future. Based on identified strengths and weaknesses we identified as key opportunities and threats 1) a high ranking and attentiveness for the research topics on the political agenda, in press and media or in public awareness, 2) availability of funding for research, 3) the resources available for creating the agenda itself, 4) the role of the sponsor of the agenda development, and 5) the continuity of stakeholder engagement as bases for identification of windows of opportunity, creating ownership for the agenda and facilitating its implementation. Our derived key recommendations are 1) a clear definition of the area for which the agenda is to be developed and for the targeted user, 2) a conceptual model to structure the agenda, 3) making clear the expected roles, tasks, input formats regarding the involvement and communication with the stakeholders and project partners, 4) a sufficient number of iterations and checks of the agenda with stakeholders to insure completeness, relevance and creation of co-ownership for the agenda, and 5) from the beginning prepare the infrastructure for the network to implement the agenda.